Amplifying Older Aboriginal and Torres Strait Islander Women's Perspectives to Promote Digital Health Equity: Co-Designed Qualitative Study - Connie Henson; Felicity Chapman; Gina Shepherd; Bronwyn Carlson; Boe Rambaldini; Kylie Gwynne (JMIR Publications, 2023)
BackgroundDigital health is becoming ubiquitous, and we must ensure equity in access. Indigenous people across most high-income countries typically have not benefited as much as other citizens from usual health care systems and technologies. Despite Aboriginal and Torres Strait Islander people's clear interest in, and enthusiastic use of, new technologies, little research has examined the needs or interests of older Aboriginal and Torres Strait Islander women. ObjectiveThis study prioritizes the perspectives of older Aboriginal and Torres Strait Islander women, tapping into their expertise associated with Indigenous ways of knowing, being, and doing, as well as their unique position within their families and communities, to design a model for using digital technologies to improve health for themselves and their families as well as their communities. MethodsOlder Aboriginal and Torres Strait Islander women from 4 partner organizations were recruited for this study. This co-designed qualitative research included citizen scientists in shaping the protocol as well as collecting, analyzing, and interpreting data. We used yarning, an Indigenous research method validated for use in health research with Indigenous people and seen as respectful and culturally safe, as a primary research tool. The use of Indigenous methodologies and our iterative process enabled us to deeply explore and incorporate perspectives from all participants and ensure that the perspectives of Indigenous citizen scientists with lived experience were privileged. The data-checking methods also used a yarning methodology, which ensured that the findings and translational model derived from the findings were validated by the participants. ResultsParticipants comprised 24 Aboriginal and Torres Strait Islander women aged ≥41 years and including 3 generations that did not grow up with the internet: seniors, baby boomers, and Generation X. The key findings in this research were that older women use various digital technologies to improve health and well-being for themselves and their families as well as their communities. Older Aboriginal women want a culturally sensitive cyberspace that caters specifically to their needs and includes relevant content and functionality that are accessible and efficient. Our translational model highlights the conditions necessary for anyone to use digital health technologies, summarizes the essential elements needed to promote equity in digital health, and illuminates the unmet needs and requirements for older Aboriginal and Torres Strait Islander women to fully benefit from digital health technologies. ConclusionsHealth is a fundamental right. As we move toward greater reliance on digital health solutions, we must recognize and address the concerns of the smaller populations of people who differ in their needs. We must urgently address the financial, connectivity, and other limiting factors highlighted by older Aboriginal and Torres Strait Islander women in this study that limit equitable access to digital health tools. International Registered Report Identifier (IRRID)RR2-10.1177/20552076221084469